The “Ten Commandments” of treating preschool children who wheeze - R.J. Green; A. Halkas; E. Weinberg (South African Family Practice)
Wheezing in young children is problematic for most practitioners. Difficulties arise in both the diagnosis and management of this clinical phenotype. Not all preschool children who wheeze have asthma. Therefore, we suggest that the “Ten Commandments” of managing preschool wheezing include thinking that in very young infants ( 1 year) wheezing is likely to be viral in origin; realising that allergy testing is mandatory to diagnose the cause of early wheezing; taking a history of asthma and allergy in family members; noting that chronic coughing is a pointer to asthma; using the term “asthma” if that is the diagnosis; ensuring that the environmental avoidance of triggers is addressed; using a short course of montelukast for virus-induced wheezing episodes; avoiding steroids to treat virus-induced wheezing; treating associated nasal symptoms; and making sure that the follow-up of children addresses the issue of stopping therapy if it is not working.